EXTREME AND TERMINAL STATES - P.F. Litvitsky ("Paediatrician" Publishers LLC, 2010)
Author brings modern conception of extreme and terminal states, their types, likenesses and differences, etiology, key common chains of pathogenesis, principles and methods of their treatment. Pathophysiological data on one of extreme states - collapse - is described in details. Next publications will present the data on shock and coma.Key words: extreme and terminal states, vicious circle of pathogenesis, extreme regulation, principles of treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):74-80)